Design, Synthesis, and Validation of a Novel [11C]Promethazine PET Probe for Imaging Abeta Using Autoradiography - Clayton A. Whitmore; Mariam I. Boules; William J. Behof; Justin R. Haynes; Dmitry Koktysh; Adam J. Rosenberg; Mohammed N. Tantawy; Wellington Pham (Molecules, 2021)
Promethazine, an antihistamine drug used in the clinical treatment of nausea, has been demonstrated the ability to bind Abeta in a transgenic mouse model of Alzheimer’s disease. However, so far, all of the studies were performed in vitro using extracted tissues. In this work, we report the design and synthesis of a novel [11C]promethazine PET radioligand for future in vivo studies. The [11C]promethazine was isolated by RP-HPLC with radiochemical purity >95% and molar activity of 48 TBq/mmol. The specificity of the probe was demonstrated using human hippocampal tissues via autoradiography.